SEMANGAT KERJA GURU DAN DAMPAKNYA PADAHASIL BELAJAR SISWA - Susmaini Susmaini (Hijri, 2019)
Sector morale teacherscan be guided by obedience to the discipline and obey all the rules of the school,Bertannggung answer to all his works in addition to the principal training andteaching, loving the work with Iklas, able to interact and provide color in the work,and able to make improvements in the work with a high spirit of work will impacton the achievement of learning outcomes with the ability of students in understanding the material of students who have Given the teacher, able todescribe the exam questions given, and able to increase the high interest inlearning so that students ' learning achievement is better.